Effects of Remnant Tissue Preservation on Clinical and Arthroscopic Results After Anatomic Double-Bundle Anterior Cruciate Ligament Reconstruction. (August 2015) - Kondo, Eiji; Yasuda, Kazunori; Onodera, Jun; Kawaguchi, Yasuyuki; Kitamura, Nobuto
Background: Clinical utility of remnant tissue preservation after single-bundle anterior cruciate ligament (ACL) reconstruction has not been established. In addition, no studies have evaluated the clinical utility of remnant preservation after anatomic double-bundle ACL reconstruction. Hypothesis: The study hypotheses were as follows: (1) Subjective and functional clinical results may be comparable between anatomic double-bundle reconstructions that preserve the remnant tissue and those that resect the remnant tissue, (2) postoperative knee stability and the second-look arthroscopic evaluation may be significantly more favorable with the remnant-preserving reconstruction, and (3) the degree of the initial graft coverage may significantly affect postoperative knee stability. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 179 patients underwent anatomic double-bundle ACL reconstruction. Based on the Crain classification of ACL remnant tissue, 81 patients underwent the remnant-preserving procedure (group P) and the remaining 98 patients underwent the remnant-resecting procedure (group R). There were no differences between the 2 groups concerning all background factors, including preoperative knee instability and intraoperative tunnel positions. The patients were followed for 2 years or more. Results: The subjective and functional clinical results were comparable between the 2 reconstruction procedures. Side-to-side anterior laxity was significantly less ( P = .0277) in group P (0.9 mm) than in group R (1.5 mm). The pivot-shift test was negative in 89% of group P and 78% of group R patients; the result for group R was significantly lower ( P = .0460). In the arthroscopic observations, results for group P were significantly better than for group R concerning postoperative laceration and fibrous tissue coverage of the grafts ( P = .0479). Conclusion: Remnant preservation in anatomic double-bundle ACL reconstruction did not significantly improve subjective and functional results in the short-term evaluation, but it significantly improved postoperative knee stability. The degree of initial graft coverage significantly affected postoperative knee stability.